2003
DOI: 10.2337/diacare.26.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Non-HDL Cholesterol as a Predictor of Cardiovascular Disease in Type 2 Diabetes

Abstract: OBJECTIVE -To determine whether non-HDL cholesterol, a measure of total cholesterol minus HDL cholesterol, is a predictor of CVD in patients with diabetes. RESEARCH DESIGN AND METHODS -The Strong HeartStudy, a population-based study of CVD and its risk factors in 13 American Indian communities in three geographic areas in the U.S. The baseline examination, conducted between July 1989 and January 1992, consisted of a personal interview, a physical examination, and laboratory tests. Of the 4,549 women and men ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
191
3
10

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(220 citation statements)
references
References 42 publications
16
191
3
10
Order By: Relevance
“…This may not be surprising, because non-HDL-C is the sum of cholesterol in LDL and TG-rich lipoproteins, and both LDL and TGrich lipoproteins are independently associated with atherosclerotic arterial changes in dialysis patients (23). The better prediction by non-HDL-C than LDL-C was also reported for the general population (37) and in the cohort including type 2 diabetes patients (38,39). Non-HDL-C level is an integrated index for atherogenic lipoproteins, and it is not affected by eating (40).…”
Section: Discussionsupporting
confidence: 60%
“…This may not be surprising, because non-HDL-C is the sum of cholesterol in LDL and TG-rich lipoproteins, and both LDL and TGrich lipoproteins are independently associated with atherosclerotic arterial changes in dialysis patients (23). The better prediction by non-HDL-C than LDL-C was also reported for the general population (37) and in the cohort including type 2 diabetes patients (38,39). Non-HDL-C level is an integrated index for atherogenic lipoproteins, and it is not affected by eating (40).…”
Section: Discussionsupporting
confidence: 60%
“…The Strong Heart Study, which addressed only American Indians, showed that non-HDL-cholesterol is a better predictor of cardiovascular morbidity than LDL-cholesterol [17]. Two further studies of people with diabetes in the USA, who were free of cardiovascular disease at baseline, comprised 921 female nurses aged <65 years [18] and 746 male health professionals aged 46-81 years [19].…”
Section: Discussionmentioning
confidence: 99%
“…Since that time, a substantial number of reports have indicated that ApoB and non-HDL-cholesterol are better predictors than LDL-cholesterol in people with diabetes [16][17][18][19]. Few studies have been conducted, however, to compare non-HDL-cholesterol with ApoB [18,19]; the studies that have been reported were restricted to North America, and the results were mixed.…”
Section: Introductionmentioning
confidence: 99%
“…It is an important measure of these particles in the presence of high triglyceride levels. The use of non-HDL-C has been demonstrated to be a better predictor of CVD events than LDL-C alone, particularly in patients with insulin resistance and/or diabetes [38,39]. For this reason, it is recommended that non-HDL-C should act as secondary target of therapy after targeting LDL-C levels in patients with increased Trg (>200 mg/dl), because the LDL-C level calculated by the Friedewald formula cannot be applied in the presence of hypertriglyceridemia [40].…”
Section: Type 2 Diabetes and Dyslipidemiamentioning
confidence: 99%